2015
DOI: 10.1155/2015/282819
|View full text |Cite
|
Sign up to set email alerts
|

Survival of AIDS Patients Treated with Traditional Chinese Medicine in Rural Central China: A Retrospective Cohort Study, 2004–2012

Abstract: This study aimed to explore the survival of AIDS patients treated with traditional Chinese medicine (TCM) in addition to combined antiretroviral therapy (cART) and of AIDS patients treated with cART. Data of patients taking cART between 30 October 2003 and 30 October 2004 in the National TCM HIV Treatment Trial Program area were retrospectively analyzed, with follow-up from 30 October 2004 to 30 October 2012. The log-rank test was used to compare survival between the two groups. A Cox proportional hazards mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The result suggested CM combined with second-line ART could better increased the survival and lengthened the lifetime of HIV/AIDS patient. In Henan, CM treatment for AIDS for tens year, many effects of TCM on HIV/AIDS have been shown, such as reducing plasma HIV viral load, increasing CD4+ T cell counts, promoting immune reconstitution, ameliorating signs and symptoms, improving the health related quality of life, and counteracting the side effects of anti-retroviral drugs [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested CM combined with second-line ART could better increased the survival and lengthened the lifetime of HIV/AIDS patient. In Henan, CM treatment for AIDS for tens year, many effects of TCM on HIV/AIDS have been shown, such as reducing plasma HIV viral load, increasing CD4+ T cell counts, promoting immune reconstitution, ameliorating signs and symptoms, improving the health related quality of life, and counteracting the side effects of anti-retroviral drugs [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TCM can reduce drug side effects, improve the immune system, clinical symptoms, quality of life, and decrease mortality [4][5].Community-acquired pneumonia (CAP) is a major contributor to morbidity and mortality even in the current HIV treatment era, especially as patients age [6].Diarrhoea is one of the most common presenting complaints in HIV-infected patients. Since the rst AIDS cases were described, a high prevalence of gastrointestinal disturbance has been reported [7][8].Meanwhile, TCM is effective and safe for the treatment of asymptomatic AIDS [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“… 17 18 As an alternative to this situation, integrative traditional East Asian medicine (ITEAM) is being used to manage these symptoms and prevent deterioration of QoL, with some significant medical effects. 19 There have been reports that acupuncture/moxibustion treatment alleviates accompanying symptoms such as peripheral neuropathy 20–22 and digestive disorders. 23 Some studies show that herbal medicine treatment is beneficial in enhancing immunity 24 25 or long-term survival rate.…”
Section: Introductionmentioning
confidence: 99%